Reproductive Outcome After GnRH Agonist Triggering With Co-Administration of 1500 IU hCG on the Day of Oocyte Retrieval in High Responders: A Long-Term Retrospective Cohort Study - Abdulkhalikova, Dzhamilyat; Bokal, Eda Vrtacnik; Stimpfel, Martin; Ciglar, Primoz; Korosec, Sara (Frontiers in Endocrinology, 2022)
While triggering oocyte maturation with GnRH agonist (GnRHa) seems to be safe and effective in terms of the risk of developing OHSS and the number of metaphase II oocytes, at the same time it results in luteal phase deficiency. To date, strategies have been developed in order to rescue defective luteal phase of GnRHa triggered cycles. The aim of our study was to assess the reproductive outcome of GnRHa triggered cycles combined with modified luteal support (1500 IU hCG at the day of oocyte retrieval) in women with high ovarian response and to compare the outcome with hCG triggered cycles in GnRH antagonist IVF-ICSI procedures. A retrospective cohort database review of the results of GnRH antagonist IVF-ICSI cycles was conducted in University tertiary-care IVF center in Ljubljana, Slovenia. A total of 6126 cycles, performed between January 1, 2014, and December 31, 2020, were included in the final analysis. Final oocyte maturation was performed with either 5000, 6500 or 10,000 IU hCG (women with normal ovarian response) or 0.6 mg GnRHa (buserelin), supplemented with 1,500 IU hCG on the day of oocyte retrieval (in women with high ovarian response). In cases of excessive ovarian response and/or high risk of OHSS, luteal support was not introduced, all good quality blastocysts were frozen. According to significant differences in patients age and number of oocytes in two groups, matching by age and number of oocytes was done. No significant differences were seen regarding pregnancy rate per ET, rate of early pregnancy loss and livebirth rate per pregnancy between the GnRHa and hCG trigger groups, respectively. A significant difference in number of developed embryos and blastocysts, as well as the number of frozen blastocysts was seen in favor of GnRHa trigger. However, the birthweight in the GnRHa trigger group was significantly lower. Conclusion: The results of our study support the use of a GnRHa trigger protocol with luteal phase rescue with co-administration of small bolus of hCG for women with high ovarian response. Such an approach in our experience results in a comparable reproductive outcome with hCG trigger group and higher frozen embryo pool.